Yttrium-90 hepatic radioembolization: clinical review and current techniques in interventional radiology and personalized dosimetry - Aaron Kian Ti Tong; Yung Hsiang Kao; Chow Wei Too; Kenneth Chin; David Ng; Pierce K. H. Chow (2016)
In recent years, yttrium-90 ((90)Y) microsphere radioembolization has been establishing itself as a safe and efficacious treatment for both primary and metastatic liver cancers. This extends to both first-line therapies as well as in the salvage setting. In addition, radioembolization appears efficacious for patients with portal vein thrombosis, which is currently a contraindication for surgery, transplantation and transarterial chemoembolization. This article reviews the efficacy and expanding use of (90)Y microsphere radioembolization with an added emphasis on recent advances in personalized dosimetry and interventional radiology techniques. Directions for future research into combination therapies with radioembolization and expansion into sites other than the liver are also explored.